Randomized clinical trials of nonpharmacological treatments - Boutron, Isabelle.; Ravaud, Philippe.; Moher, David, 1957- (Chapman & Hall/CRC biostatistics series, 2012)
"Nonpharmacological treatments include a wide variety of treatments such as surgery, technical procedures, implantable devices, nonimplantable devices, rehabilitation, psychoteherapy, and behavioral interventions. This book focuses on the methods of assessing nonpharmacological treatments, highlighting specific issues and discussing all possible design of trials. It provides practical examples to underline the issues and solutions in assessing nonpharmacological treatment in trials. Arguably the first book to exclusively explore this topic, it discusses various categories of treatments from surgical procedures to psychotherapy"--Provided by publisher.